Identification of zingiber components by gas chromatograph/mass spectrometer and semi-empirical calculations - Sarhan Mahmoud Abd El kareem, Mamoun; Abd El fattah Rabbih, Mohamed; Taha Mohamed Selim, Ezzat (International Journal of Physical Research, 2016)
The important used of Zingiber in different fields such as medicine and foods, this leads to study the physical and chemical properties of its components. The chemical components in Zingiber officinale Roscoe were identified by gas chromatograph/ mass spectrometer (GC/MS) with electron ionization mode. The major components of Zingiber under investigation namely: (1) Pentadecanoic acid (2) 1,3-Dioxepane, 2-pentadecyl (3) 4H-Pyran-4-one, 2,3-dihydro-3,5-dihydroxy-6-methyl (4) gingerol. Electron ionization mass spectra of these compounds have been obtained and investigated. In addition, the semi-empirical (MNDO) method was used to calculate some physical and thermochemical properties for the structural of these compounds such as total energy, electronic energy, ionization energy, heats of formation, proton affinity and dipole moments which might to predict the activity and behavior of these compounds.